Analysis of students' mathematical problem solving ability as the effect of constant ill-structured problem's employment. (February 2019) - Araiku, J; Parta, I N; Rahardjo, S
Abstract: This study aimed to give more detailed comprehension on how students' mathematical problem solving ability improved when ill-structured problem constantly employed for a particular period of time. The study was descriptive qualitative research and conducted in MTs Surya Buana, Malang, East Java, Indonesia. The subject consisted of 27 students from eighth-grade, where they were distributed into 7 groups of 3 or 4. The most significant improvements were students gained new skill in (1) formulating problems as well as new insight on seeing all possibilities in solving problems; (2) constructing resolution plan; (3) doing investigation as well as judging the validity of the information retrieved; and (4) evaluating solutions according to mathematical concepts. Based on these results, the use of ill-structured problem and active scaffolding from the teacher are highly recommended in mathematics instruction.